Energy efficient measures to reduce electrical energy use in commercial buildings in New York City (2015)
GEA Consulting Engineers, acting as the design engineers, was hired by the owner, East Village 207 Residential LLC2 for energy modeling for compliance with LEED NC V3 -- This report details the results of the energy simulation done with the 100% construction documents -- This report only refers to entities within the LEED3 project boundary -- The project consists of a new eight-story high-end residential condominium building with 81 units, as shown in illustration 1, and approximately 117,905 GSF, equivalent to 10,953.73 m2, is located at 211 E 13th Street in New York, NY -- The residential portion of the building will function 24-7 -- The design goal is to utilize energy efficient measures to reduce electrical energy use and aims to achieve LEED certification -- LEED EA Credit 14 requires a building to demonstrate a percentage improvement in the proposed building performance compared with the baseline building -- The Credit rewards 1 point for achieving 12% reduction in energy costs -- Additionally, the Credit rewards another point for each subsequent reduction of 2% in the building’s energy cost